Construction of Electrocatalytic and Heat-Resistant Self-Supporting Electrodes for High-Performance Lithium–Sulfur Batteries - Zhang, Xuemei; Wei, Yunhong; Wang, Boya; Wang, Mei; Zhang, Yun; Wang, Qian; Wu, Hao (Nano-Micro Letters, 2019)
Boosting the utilization efficiency of sulfur electrodes and suppressing the “shuttle effect” of intermediate polysulfides remain the critical challenge for high-performance lithium–sulfur batteries (LSBs). However, most of reported sulfur electrodes are not competent to realize the fast conversion of polysulfides into insoluble lithium sulfides when applied with high sulfur loading, as well as to mitigate the more serious shuttle effect of polysulfides, especially when worked at an elevated temperature. Herein, we reported a unique structural engineering strategy of crafting a unique hierarchical multifunctional electrode architecture constructed by rooting MOF-derived CoS2/carbon nanoleaf arrays (CoS2–CNA) into a nitrogen-rich 3D conductive scaffold (CTNF@CoS2–CNA) for LSBs. An accelerated electrocatalytic effect and improved polysulfide redox kinetics arising from CoS2–CNA were investigated. Besides, the strong capillarity effect and chemisorption of CTNF@CoS2–CNA to polysulfides enable high loading and efficient utilization of sulfur, thus leading to high-performance LIBs performed not only at room temperature but also up to an elevated temperature (55 °C). Even with the ultrahigh sulfur loading of 7.19 mg cm−2, the CTNF@CoS2–CNA/S cathode still exhibits high rate capacity at 55 °C. Highlights: 1 Flexible hierarchical electrode architecture was constructed by rooting MOF-derived CoS2/carbon nanoleaf arrays into a nitrogen-rich 3D conductive scaffold. 2 An accelerated electrocatalytic effect and improved polysulfide redox kinetics arising from the structure advantages were investigated. 3 As-prepared composite delivers a significantly improved electrochemical performance not only at room temperature but also at elevated temperature.